Efeito do extrato padronizado das flores de Cassia fistula linn. (chuva-de-ouro) sobre o processo de cicatrização in vitro e in vivo e elucidação do possível mecanismo de ação - Martins, Taiana Magalhães Pierdoná (2019)
The burden of wound care has been increasing in recent decades. Medicinal plants have become an excellent resource for this purpose due to their low cost, easy access and therapeutic effectiveness. Cassia fistula Linn (golden rain) is a plant found in Brazil's tropical regions and popularly known to treat skin diseases, itching, and diabetes. Previous studies have shown that the extract of C. fistula flowers has demonstrated antioxidant, antibacterial and antifungal activities. Phenolic compounds from C. fistula were also useful in wound healing. Thus, this work aimed to characterize the ethanolic extract of C. fistula flowers (ECFF) and to investigate its effect in murine fibroblast (L929) and macrophages (RAW 264.7) and human keratinocytes (HaCaT). Besides, the objective was to evaluate its effect in mice using a model of excisional wounds. The phytochemical characterization of ECFF showed alkaloids, phenols, flavonoids, tannins and anthraquinones, and through ultra-performance liquid chromatography (UPLC), the presence of rutin, kaempferol-3-O-rutinoside, kaempferol and reina. In this study, ECFF (31.25 - 250 µg / mL) improved the cell viability and increase the cell mitochondrial metabolism in L929 and HaCaT, using the MTT method. Through the SRB assay and in vitro wound healing, ECFF showed an increase in HaCaT proliferation and migration. These effects may be associated with E-cadherin decrease, measured by flow cytometry. ECFF demonstrated an antioxidant effect by the DPPH method, protected fibroblasts from oxidative stress induced by H2O2, and increased the VEGF, an angiogenesis factor, as well. In RAW 264.7 macrophages, ECFF decreased nitrite levels released after LPS stimulation and modulated the cytokines TNF-α, IL-1β, IL-10 and growth factor TGF-β release. The cream produced with ECFF (CrECFF 12.5 and 25% w/w) increased TNF-α and IL-1β levels after 2 days of treatment on excision wound model, and the result was confirmed by immunohistochemical analysis. In addition, CrECFF promoted a significant contraction of the wounds after 4, 7 and 9 days of treatment, stimulating reepithelialization. After 7 days of treatment, CrECFF was able to increase TGF-β levels. Therefore, the wound healing effect of ECFF can be attributed to the reduction of damage induced by oxidative stress, modulating the inflammation and wound repair stimulus. We believe that this work will support other studies to develop an herbal medicine from ECFF for the wound’s treatment.